Privileges of an Integrated Approach in Sports Morphology to the Analysis of the Physical Development of Juniors and Cadets Involved in Sports (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Based on medical anthropology, one can judge the levels of physical development of an athlete, which allows you to control the health status of junior and cadet athletes at all stages of its development. The integrated approach of medical anthropology using sports morphology to the analysis of the physical development of juniors and cadets involved in sports makes it possible to achieve higher sports results and fully appreciate the positive dynamics of physiological development.